Irfānī Epistemology and Indonesian Islam from Jabiri’s Fragmentation to Neo-Sadra’s Integration: An Islamic Philosophical Approach - Al Walid, Kholid; Miri, Mohsen; Rijal, Syamsul; Gama, Cipta Bakti; Norman, Nurul Ain (Universitas Islam Negeri Mataram, 2024)
This research departs from the conflict between Jabiri's fragmented geo-epistemology and his antipathy towards ‘irfānī epistemology, vis a vis the character and style of Indonesian Islamic reasoning. The strong influence of Jabiri's thoughts in this country makes it important to answer the question of the development of the discourse on the criticism of Arab Islamic reasoning, how Indonesian figures absorb his thoughts, and how to develop them in the future. Using the qualitative method and an Islamic philosophical approach, this research comes to the following conclusions: first, Jabiri's fragmented geo-epistemology is not consistent with its initial holistic vision, is stuck in a selective attitude, fails to appreciate Eastern Islamic culture, and rests on assumptions of rationality that lack depth. Second, Jabiri's influence in Indonesian Islamic discourse has not made local figures adhere to a fragmented epistemology, nor have they become antipathetic towards ‘irfānī reasoning. Third, the development of integrative epistemology and 'irfānī epistemology in Indonesian Islamic reasoning can be enriched with a foothold on Neo-Sadra philosophical models. All data in this study were collected using library research methods.